Bridging the gap: A comparative study of primary school students’ language needs and textbook suitability - Workineh, Zeleke; Genanew, Mekuriaw; Delele, Aragaw; Minayehu, Debritu (Injibara Journal of Social Science and Business, 2025)
This research project aimed at exploring the nexus between primary school students' English language learning needs and textbook contents. To achieve the research objective descriptive survey design was employed, and teachers’ and students’ samples were included by using a simple random sampling technique. Accordingly, 338 teachers and 783 students were selected for the study sample. The instruments of data collection were questionnaires, document analysis, and interviews. By using these methods of data collection, the findings were that the course contents in English textbooks were beyond students’ level and their language needs as foreign language learners. Also, the various activities and the course contents were not graded well from simple to complex levels. Lastly, the textbook preparation did not significantly address students’ English language needs at the lower cycle primary education level. In considering the findings of the study, the following recommendations were given. First, the textbook developers should prepare English textbooks for the first cycle of primary education in considering students’ levels. Second, the textbook developers should assess the students’ need for English Foreign Language in the first cycle of primary school. Finally, researchers should study further the status of teachers’ efforts to minimize the gap between students’ need of English learning needs and the textbook preparations.